Timing of Pars Plana Vitrectomy in Management of Gunshot Perforating Eye Injury: Observational Study - Hammouda Hamdy Ghoraba; Mohamed Amin Heikal; Hosam Osman Mansour; Haithem Mamon Abdelfattah; Emad Mohamed Elgemai; Adel Galal Zaky (Journal of Ophthalmology)
The aim of this study is to report the difference in either anatomical or functional outcome of vitreoretinal intervention in cases of gunshot perforating eye injury if done 2–4 weeks or after the 4th week after the original trauma. Patients were treated with pars plana vitrectomy and silicon oil. Surgeries were performed in the period from February 2011 until the end of December 2014. 253 eyes of 237 patients were reviewed. 46 eyes were excluded. 207 eyes of 197 patients were analyzed. The included eyes were classified based on the timing of vitrectomy in relation to the initial trauma into two groups: 149 eyes (the first group) operated on between the 3rd and the 4th week and 58 eyes (the second group) operated on after the 4th week after the trauma. Following one surgical intervention, in the first group, attached retina was achieved in 93.28% of patients. In the second group, attached retina was achieved in 96.55% of patients. All RD cases could be attached by a second surgery. Visual acuity improved in 81.21% of patients, did not change in 15.43% of patients, and declined in 3.35% of patients. In the second group, visual acuity improved in 81.03% of patients, did not change in 12.06% of patients, and worsened in 6.89% of patients. There was no statistically significant difference between the two groups in either anatomical or functional results. We recommend interfering before the 5th week after the trauma as retinal detachment is encountered more in cases operated on after the 4th week. The visual outcome depends on the site of entry and exit (the route of gunshot).